A preliminary study of cortical morphology changes in acute brainstem ischemic stroke patients. Issue 1 (8th January 2021) - Chen, Huiyou; Shi, Mengye; Geng, Wen; Jiang, Liang; Yin, Xindao; Chen, Yu-Chen
Abstract : Abstract: The study aimed to explore the cortical thickness and gyrification abnormalities in acute brainstem ischemic patients in both the ipsilateral and contralateral hemisphere compared with healthy controls. Structural magnetic resonance imaging data were prospectively acquired in 48 acute brainstem ischemic patients, 21 patients with left lesion and 27 with right lesion, respectively. Thirty healthy controls were recruited. Cortical morphometry based on surface-based data analysis driven by CAT12 toolbox implemented in SPM12 was used to compare changes in cortical thickness and gyrification. Significant decreases of cortical thickness loss were found in bilateral cerebral hemispheres of the brainstem ischemic patients compared to the healthy controls ( P < .05, family-wise error (FWE)-corrected). We also found significant gyrification decreases in the insula, transverse temporal, supramarginal of the ipsilateral on hemisphere in the right brainstem ischemic patients compared to the healthy controls ( P < .05, FWE-corrected). Brainstem ischemic patients have widely morphological changes in the early phase and may be helpful in designing individualized rehabilitative strategies for these patients.